2016
DOI: 10.1063/1.4962107
|View full text |Cite
|
Sign up to set email alerts
|

Thermal regulation of building-integrated concentrating photovoltaic system using phase change material

Abstract: Abstract. Thermal regulation of building-integrated concentrating photovoltaic (BICPV) systems have a direct influence on the photovoltaic performance. This paper investigates the thermal behavior of a BICPV and phase change material (PCM) system through numerical modeling simulations. Based on an updated mathematical model, theoretical simulation has been conducted for a BICPV-PCM system. The results show a 3% electrical efficiency improvement of the BICPV-PCM system in certain cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Few studies have been found that apply this cooling technique in the CPV applications [45,46]. Al Siyabi et al [45,47] have numerically conducted a thermal analysis using an MLM heat sink in a single solar cell receiver. They considered a non-uniform heat source for the MLM heat sink.…”
Section: Of 25mentioning
confidence: 99%
“…Few studies have been found that apply this cooling technique in the CPV applications [45,46]. Al Siyabi et al [45,47] have numerically conducted a thermal analysis using an MLM heat sink in a single solar cell receiver. They considered a non-uniform heat source for the MLM heat sink.…”
Section: Of 25mentioning
confidence: 99%